Opioid Receptor Interacting Proteins and the Control of Opioid Signaling - T. Lamberts, Jennifer; R. Traynor, John (Current Pharmaceutical Design, 2013)
Opioid receptors are seven-transmembrane domain receptors that couple to intracellular signaling molecules by activating heterotrimeric G proteins. However, the receptor and G protein do not function in isolation but their activities are modulated by several accessory and scaffolding proteins. Examples include arrestins, kinases, and regulators of G protein signaling proteins. Accessory proteins contribute to the observed potency and efficacy of agonists, but also to the direction of signaling and the phenomenon of biased agonism. This review will present current knowledge of such proteins and how they may provide targets for future drug design.
Keywords: drug discovery